Variability in the diet of cape fur seals and their interaction with fisheries off the South African coast, 2010-2019 - Gumede, Nosipho Clementine (Department of Biological Sciences, 2025)
Cape fur seals (Arctocephalus pusillus pusillus) are sentinel marine top predators in southern African coastal waters due to their generalist diet and wide breeding range from southern Angola (Baia dos Tigres) to Algoa Bay, South Africa. Their long-life span makes them good indicators of ecosystem health by providing insights on ecological interactions in the food webs of the South African marine ecosystem, and on the variation in the availability of prey resources. This dissertation describes the diet of Cape fur seals off the South African coast between 2010 and 2019 based on the analysis of scats collected at 11 South African colonies from Kleinsee (29°39' S, 17°04' E) to Robberg Ledges (34º03' S, 23º22' E). The colonies were divided into three geographical regions: St Helena Bay, Saldanha Bay to Cape Agulhas, and east of Cape Agulhas. Potential competition for prey fish between the Cape fur seal and fishery catches was also investigated. Catches by the purse-seine fishery landed at Lambert's Bay, Saldanha Bay and Gansbaai were compared with the diet of fur seals at nearby colonies (Lambert's Bay, Jutten Island and Geyser Rock, respectively). The importance of small pelagic fish in the Cape fur seal diet also was compared to acoustic biomass estimates of these key fish species. A total of 4165 scat samples were used to infer spatial and temporal variation in the Cape fur seal diet. Fish otoliths, cephalopod beaks and seabird feathers were used to identify prey to the lowest taxonomic level possible, and the mass and length of fish prey were estimated from otolith lengths using regression equations. Fifty-three prey taxa (43 fish, 6 cephalopods, 4 seabirds) were identified from scats, and indices of relative importance (%IRI), mass contribution (%M), numerical abundance (%NA), and frequency of occurrence (%FO) were used to determine the importance of each prey taxon to the diet. Fish dominated the diet (88.0%FO) followed by seabirds (9.1%FO), cephalopods (5.5%FO) and crustaceans (0.4%FO). In decreasing order of importance and in terms of %NA, the most important prey species were anchovy (Engraulis encrasicolus capensis), horse mackerel (Trachurus trachurus capensis), sardine (Sardinops sagax) and hake (Merluccius capensis and M. paradoxus). Anchovy dominated the diet across all study areas and years, while other species varied in importance over the study years. There was seasonal variation in the diet across all three regions, with anchovy being consumed more during winter (non-upwelling season) than summer. Almost all other fish taxa were consumed more during summer in all the three study regions. Larger prey such as hake and horse mackerel contributed less to the diet; in terms of mass contribution (10.9%M and 10.3%M, respectively) than the smaller anchovies and sardines (combined 68.8%M). Scat samples were compared with stomach content samples obtained from 1974 to 1996. There were no changes in diet composition (fish, cephalopods, crustaceans, seabirds) between the different study periods or the different diet analysis methods. However, there were changes in proportions of prey type consumed; seabirds were consumed less during 1974 - 1996 compared with 2010 to 2019. Pelagic goby (Sufflogobius bibarbatus) (55.0%NA) dominated the diet in 1974 – 1996, while anchovy (67.6%NA) predominated in 2010– 2019. Only 30 prey taxa (22 fish, 5 cephalopods, 2 crustaceans, 1 seabird) were identified from 2 336 stomach content samples, compared with 53 from scats. Although there is some uncertainty due to the different methods, it seems that prey proportions have changed between the two periods. Among the commercial targeted pelagic species (i.e. sardine and horse mackerel), Cape fur seals and purse-seine fisheries mainly targeted juvenile to adult fish, except for anchovy, where fisheries caught much smaller fish. There was an overlap in fish size distribution (50 – 200 mm) of sardine and red-eye (Etrumeus whiteheadi) found in seal scats and commercial landings records. A positive correlation was found between spawner acoustic biomass estimates and the importance (%NA) of anchovy and sardine in the Cape fur seal diet. The importance of sardine decreased in contribution when biomass estimates were low. Similarly, anchovy importance in the diet was positively correlated with biomass estimates. However, the overall consumption of anchovy did not correlate with the estimated biomass, but there was correlation between sardine consumption and the biomass estimate. Cape fur seals seemingly could switch between prey depending on the available biomass. This was evident in the study colonies and during the study periods. This study demonstrates that the diet of Cape fur seal has remained relatively unchanged since 1974. They have largely increased the proportions of species they consume based on abundance. The consistent presence of anchovy in the diet of Cape fur seals over time suggests that this fish species constitutes an important food item for fur seals. In general, there was no competition between the purse-seine fishery and Cape fur seals. The difference in anchovy sizes caught by the fishery (45 – 130 mm) and seals (17 – 250 mm) indicate that there may be less competition than previously thought. However, purse-seine fishery and seals both target similar sizes (21.9 – 250 mm) of red eye and sardine. Increases in the presence of seabirds in the diet since 1974 have implications for three species of Endangered seabirds: African Penguins (Spheniscus demersus), Cape Gannets (Morus capensis) and Cape Cormorants (Phalacrocorax capensis). Overall, the study demonstrated some long-term changes in the diet of Cape fur seals over the past 40 years despite the use of two different sampling methods and the spatially patchy data.